The Role of Public Relations in Managing and Delivering Information to the Public - Risma Niswaty; Ade Nurul Ayu Aras; Sirajuddin Saleh (Journal of Social Science and Economics (JOSSE), 2024)
This research aims to find out how the role of public relations in managing and conveying information to the people of Pinrang Regency is described. This research is qualitative, therefore to achieve the research objectives, data collection techniques are used, namely observation, interview and documentation techniques. There were 3 informants, namely the Head of the Public Communication Media Management Section, the Head of the Public Communication Media Management Section and the Staff of the Public Communication Media Management Section.The results of the study show that the role of public relations as a communication expert is tasked with conveying information to the public while receiving various directions and inputs from the Community Information Group (KIM). Public Relations as a problem solving process facilitator as a routine problem-solving facility carries out intense coordination with each KIM in each sub-district. Public Relations as a Communication Facilitator is tasked with establishing cooperative relationships with social media practitioners, actively and participatorically interacting with the community and providing understanding to the community and lastly, public relations as a Technician Facilitator is tasked with analyzing activities carried out by the community, including those that have a positive impact on the community itself, reporting on activities carried out by the community. This study proves that the implementation of the role of Public Relations in managing and conveying information to the community is going well so that the people of Pinrang Regency can get the information they need properly and appropriately.